Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species - Shi, Weifang; Tong, Xiaoli (Zootaxa, 2019)
Six species of Bungona Harker, including three species of the subgenus Centroptella Braasch & Soldán and three species of subgenus of Chopralla Waltz & McCafferty, are reported from China. Of which, three new species, Bungona (Centroptella) ovata sp. nov., Bungona (Centroptella) quadrata sp. nov. and Bungona (Chopralla) bifida sp. nov., are described based on nymphal materials. In addition, Bungona (Chopralla) liebenauae (Soldán, Braasch & Muu, 1987) that was previously known only from Vietnam is newly recorded in China. An identification key to Bungona species known from Oriental Region is presented.